Matching Phosphorus Fertilizer Types with Soil Type in Rice Cultivation Optimizes Yield, Soil Phosphorus Availability, and Phosphorus Fertilizer Use Efficiency - Shiyu Peng; Xinyao Zhang; Le Sun; Rushan Chai; Chaochun Zhang; Xiaohui Chen; Laichao Luo; Kadambot H. M. Siddique (Agriculture)
Inefficient phosphorus (P) fertilizer application often accumulates soil P, wasting valuable phosphate resources and contributing to environmental pollution. Given the suboptimal P fertilizer use efficiency (PUE), understanding soil P dynamics and selecting appropriate fertilizers is crucial. Fluvo-aquic soil and yellow-cinnamon soils were used in a rice pot trial to compare five P fertilizer types: single superphosphate (SSP), diammonium phosphate (DAP), calcium magnesium phosphate (CMP), triple superphosphate (TSP), and ammonium polyphosphate (APP), alongside a no P, control (CK). In fluvo-aquic soil, TSP and APP significantly increased rhizosphere P availability at anthesis, while SSP increased yield and shoot P accumulation at maturity. In yellow-cinnamon soil, DAP had the highest rhizosphere P availability at anthesis, while APP significantly increased shoot P accumulation at anthesis and shoot P accumulation and grain yield at maturity. Moreover, PUE was highest with SSP and CMP in fluvo-aquic soil and APP and TSP in yellow-cinnamon soil. Throughout the experiment, increased soil alkaline phosphatase activity promoted NaOH-Po conversion to NaHCO3-Pi, increasing rice shoot P uptake, yield, and PUE in both soils. Based on the above findings, it is recommended to apply SSP and TSP to fluvo-aquic soil and APP and TSP to yellow-cinnamon soil to achieve higher yield and PUE, which can be further confirmed by subsequent field-scale studies.